PENGARUH PRICE EARNING RATIO, DIVIDEND PAYOUT RATIO, VOLUME PERDAGANGAN, DAN NILAI TUKAR TERHADAP VOLATILITAS HARGA SAHAM PADA PERUSAHAAN KONSTRUKSI BANGUNAN YANG TERDAFTAR DI BEI - Diajeng Reztrianti; Budhi Suparningsih (Jurnal Ekonomi dan Industri, 2021)
This study aims to determine the relationship between price earning ratio, dividend payout ratio, trading volume, and exchange rate on stock price volatility in building construction companies listed on the Stock Exchange, where this study uses a qualitative and quantitative design. Partially Dividend payout ratio has no significant effect on stock price volatility. Price earning ratio has a significant effect on stock price volatility. Trading volume has no significant effect on stock price volatility. The exchange rate has a significant influence on the volatility of stock prices. Simultaneously, price earning ratio, dividend payout ratio, trading volume and exchange rate have a significant influence on stock price volatility.